Optimal Timing of Tax Policy in the Face of Projected Debt Increases - Chris Ball; John Creedy; Grant Scobie (New Zealand Government, The Treasury, 2016)
This paper examines the optimal time path of the tax rate, in a model where an increasing ratio of government debt to GDP is projected in the absence of policy changes.
Keywords: H62; H63; H68; 330; Tax policy; Stochastic projections; Debt ratio; Haushaltsdefizit; Bruttoinlandsprodukt; Steuerpolitik; Optimale Besteuerung; Steuerwirkung; Theorie